Interaksi Investasi Asing Langsung, Dinamika Pasar Tenaga Kerja, Dan Keberlanjutan Lingkungan Dalam Membentuk Ketahanan Ekonomi Di Pasar Berkembang - Afidatuzzakiah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study investigates the complex interactions between foreign direct investment (FDI), labor market dynamics, and environmental sustainability in shaping economic resilience in developing countries. Drawing on panel data spanning 2010 to 2023 and employing advanced analytical techniques, including structural equation modeling (SEM) and dynamic panel regression, the research examines both direct and indirect effects of FDI on economic resilience. The results indicate that FDI significantly contributes to strengthening economic stability, while labor market conditions act as a critical mediator, amplifying the benefits of investment through skill development, employment generation, and workforce adaptability. Additionally, environmental sustainability reinforces the positive impact of FDI, suggesting that integrating ecological considerations with economic and social policy enhances long-term resilience. The findings underscore the importance of coordinated policy frameworks that promote inclusive labor practices, sustainable industrial development, and strategic investment inflows, thereby supporting the sustainable growth and stability of developing economies.